(untitled) (Czech Journal of International Relations, 2021)
An emerging literature has shown concerns about the impact of the pandemic on the proliferation of digital surveillance. Contributing to these debates, in this paper we demonstrate how the pandemic facilitates digital surveillance in three ways: (1) By shifting everyday communication to digital means it contributes to the generation of extensive amounts of data susceptible to surveillance. (2) It motivates the development of new digital surveillance tools. (3) The pandemic serves as a perfect justification for governments to prolong digital surveillance. We provide empirical anecdotes for these three effects by examining reports by the Global Digital Policy Incubator at Stanford University. Building on our argument, we conclude that we might be on the verge of a dangerous normalization of digital surveillance. Thus, we call on scholars to consider the full effects of public health crises on politics and suggest scrutinizing sources of digital data and the complex relationships between the state, corporate actors, and the sub-contractors behind digital surveillance.